Konstruksi Metodologis Tafsir Ayat Hukum Sūrat Al-Anʿām: Studi atas Independensi Pemikiran Hukum Imam Al-Ṭabarī - Al-Amin; Abdullah Firdaus; Nurung; Nia Nursaktila (Kartika: Jurnal Studi Keislaman, 2026)
This article examines the originality of Al-Ṭabarī's interpretation of legal verses in Sūrat Al-Anʿām through library research employing a qualitative-descriptive approach and comparative analysis. Primary data are derived from Al-Ṭabarī's exegetical work, Jāmiʿ al-bayān fī taʾwīl al-Qurʾān, while secondary sources include tafsir literature, journals, and studies on classical exegetical methodology. The analysis proceeds by identifying legal verses, classifying legal topics, analyzing Al-Ṭabarī's interpretive method, and comparing it with other classical exegetes. The findings reveal four dimensions of Al-Ṭabarī's originality: first, a novel methodology integrating tafsīr bi al-maʾthūr with controlled rational analysis (raʾy); second, contextualization of meaning in relation to Arab social reality; third, critique of weak opinions, whether due to deficient chains of transmission (sanad) or contextual inappropriateness; and fourth, juridical tarjīḥ (preferential weighting) regarding exceptions under exigent circumstances. Al-Ṭabarī's rational istinbāṭ (deduction) is both methodological and argumentative—innovative not only in transmitting tradition but also creative in organizing narrations toward a systematic legal framework. This study affirms Al-Ṭabarī's significant position in the development of classical legal exegesis and highlights his contribution to a normative-argumentative interpretive model that influenced subsequent exegetes, while also opening space for re-reading legal construction within the turāth (heritage).